2021
DOI: 10.3389/fenvs.2021.628214
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Uncertainty in Land-Use/Land-Cover Classification Accuracy: A Stochastic Simulation Approach

Abstract: In numerous applications of land-use/land-cover (LULC) classification, the classification rules are determined using a set of training data; thus, the results are inherently affected by uncertainty in the selection of those data. Few studies have assessed the accuracy of LULC classification with this consideration. In this article, we provide a general expression of various measures of classification accuracy with regard to the sample data set for classifier training and the sample data set for the evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This disparity can be attributed to the error matrix, which indicates that some of the proportion of the area of agricultural land is omitted from the map. These results are in line with other similar studies that have also demonstrated the improved accuracy of area estimation by considering the uncertainty in the error matrix and confidence interval [198][199][200].…”
Section: Discussionsupporting
confidence: 92%
“…This disparity can be attributed to the error matrix, which indicates that some of the proportion of the area of agricultural land is omitted from the map. These results are in line with other similar studies that have also demonstrated the improved accuracy of area estimation by considering the uncertainty in the error matrix and confidence interval [198][199][200].…”
Section: Discussionsupporting
confidence: 92%
“…Since the confusion matrix is preferred in measurement analysis in many study analyses, it was also used in this study. The metrics that make up the confusion matrix are as follows: accuracy (Acc), sensitivity (Se), specificity (Sp), precision (Pre), and F -score ( F -Scr) (Cheng et al, 2021; Polat et al, 2020). The following equations are used to calculate the metrics.…”
Section: Experimental Analysis and Resultsmentioning
confidence: 99%